2021
DOI: 10.3390/rs13050963
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Global Gross Primary Production from Sun-Induced Chlorophyll Fluorescence Data and Auxiliary Information Using Machine Learning Methods

Abstract: The gross primary production (GPP) is important for regulating the global carbon cycle and climate change. Recent studies have shown that sun-induced chlorophyll fluorescence (SIF) is highly advantageous regarding GPP monitoring. However, using SIF to estimate GPP on a global scale is limited by the lack of a stable SIF-GPP relationship. Here, we estimated global monthly GPP at 0.05° spatial resolution for the period 2001–2017, using the global OCO-2-based SIF product (GOSIF) and other auxiliary data. Large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…The spatial resolution of the NIRv‐GPP is 0.05°. Recent studies have indicated the excellence of the NIRv‐GPP (Bai et al, 2021; Wang et al, 2020). This data set was downloaded from the National Tibetan Plateau Data Center (http://data.tpdc.ac.cn).…”
Section: Methodsmentioning
confidence: 99%
“…The spatial resolution of the NIRv‐GPP is 0.05°. Recent studies have indicated the excellence of the NIRv‐GPP (Bai et al, 2021; Wang et al, 2020). This data set was downloaded from the National Tibetan Plateau Data Center (http://data.tpdc.ac.cn).…”
Section: Methodsmentioning
confidence: 99%
“…The Moderate Resolution Imaging Spectroradiometer (MODIS) GPP is widely used for global and regional change analysis because of its continuous estimation (Chen et al., 2019; Ding et al., 2020; Jiao et al., 2021). Although MODIS collection 6 (C6) GPP has resolved the problem of aging of sensors (Lyapustin et al., 2014), it currently remains some controversy regarding the use of MODIS GPP; for example, it underestimates the vegetation GPP (Bai et al., 2021; Du et al., 2018; Qiu et al., 2020; Zhang et al., 2017). In addition, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…numerous models have been developed to simulate GPP (e.g., light energy use efficiency (LUE) models and process-based models), and several global GPP products have been derived (Bai et al, 2021;Jiang & Ryu, 2016;Jung et al, 2011;Running et al, 2015;Tagesson et al, 2021;Tramontana et al, 2016;Wang et al, 2021;Yuan et al, 2010;Zhang et al, 2017). For example, the Global LAnd Surface Satellite (GLASS) GPP is a long-time series, high accuracy, global surface GPP product derived from multi-source data and ground-based observations (Yuan et al, 2007(Yuan et al, , 2010.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of auxiliary information to enhance the performance of estimation procedures is well documented in the statistical and allied sciences literature, see for example, Zhang and Chambers (2004), Chou et al (2017) and Bai et al (2021). In practice auxiliary information is obtainable from various sources, such as census, survey reports and expert opinion, see also Rao et al (1990) and Biemer and Peytchev (2013).…”
Section: Motivationmentioning
confidence: 99%